Direct coagulation casting of silicon nitride suspension via a dispersant reaction method. Issue 3 (15th February 2016) - Gan, Ke; Xu, Jie; Zhang, Xiaoyan; Huo, Wenlong; Yang, Minghao; Qu, Yanan; Yang, Jinlong
Abstract: A direct coagulation casting method for silicon nitride suspension via dispersant reaction was reported. Tetramethylammonium hydroxide (TMAOH) was used as dispersant to prepare silicon nitride suspension with high solid loading and low viscosity. Influences of TMAOH and pH value on the dispersion of silicon nitride powder were investigated. Glycerol diacetate (GDA) was used to coagulate the silicon nitride suspension. Influences of the concentration of glycerol diacetate on the viscosity and pH value of the suspension were investigated. It was indicated that high viscosity sufficient to coagulate the suspension was achieved by adding 1.0–2.0 vol% glycerol diacetate at 40–70 °C. The coagulation mechanism was proposed that the silicon nitride suspension was destabilized by dispersant reacting with acetic acid which was hydrolyzed from glycerol diacetate at elevated temperature. Coagulated samples could be demolded without deformation by treating 50 vol% silicon nitride suspensions with 0.2 wt% tetramethylammonium hydroxide and 1.0–2.0 vol% glycerol diacetate at different temperatures. Dense silicon nitride ceramics with relative density above 98.8% had been prepared by this method using glycerol diacetate as coagulating agent sintered by different methods.